PENGARUH KUALITAS PELAYANAN DAN SALURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN (Studi dilakukan di PT. PLN (Persero) Area Pamekasan Rayon Pamekasan) - Gery Harseno (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine simultaneous, partial and dominant effects of servant quality dimensions, i.e. Reliability (X1), Assurance (X2), Tangibless (X3), Empathy (X4), Responsiveness (X5), and Marketing Channel (X6) on Customer Satisfaction (Y) in PT. PLN (Persero) in the area of Pamekasan in the sub area of Pamekasan. Yhe sample of this quantitative descriptive research is 100 respondents selected from the population using Slovin formula. The research location in the Regency of Pamekasan. The instrumens of this study are assessed using validity and reliability testing. The data are analyzed using multiple regression. The results show that dimensions of service quality and marketing channel give a significant influence on the satisfaction of the customers of PT. PLN (Persero) in the area of Pamekasan in the sub area of Pamekasan, from which responsiveness is the dominant variable.Keywords : Reliability, Assurance, Tangibless, Responsiveness, Marketing Channel, Customer Satisfaction.